Efficiency of bacteria and bacterial assisted phytoremediation of heavy metals: An update. (May 2021) - Sharma, Pooja
Graphical abstract: Highlights: We review the literature on the role of bacteria in metals phytoremediation. Bacteria stimulate plant growth in unfavourable environmental conditions. Bacteria-assisted phytoremediation for the restoration of polluted wastewater. Bacterially, phytoremediation aid is offered field experiments can be facilitated. Abstract: The aim of this review to address the plant-associated bacteria to enhance the phytoremediation efficiency of the heavy metals from polluted sites and it is also highlighted advances for the application in wastewater treatment. Plant-associated bacteria have potential to encourage the plant growth and resistance under stress conditions. Such bacteria could enhance plant growth by controlling growth hormone, nutrition security, producing siderophore, secondary metabolites, and improving the antioxidant enzymes system. This review also explores the concepts and applications of bacteria assisted phytoremediation, addressing aspects that affect phytoremediation and pathways for restoration. Significant review issues relating to production and application of bacteria for improvement of bioremediation were established and presented for possible future research. Bacteria assisted phytoremediation is cost-effective strategy and metal sequestration mechanism that hold high metal biosorption capacities. This also takes into consideration the current state of technology implementations and proposals for prospective clean-up studies.